Evaluation of factors important to enhance productivity. Issue 1 (31st December 2016) - Kumar, Sanjay; Duhan, Manish; Haleem, Abid
Abstract: Productivity as a measure for output is important to industry and academia. In this research, factors to enhance productivity have been identified from the literature by reviewing various international and national sources to explore this evergreen field of research that is "productivity, " which has always been an increasingly interesting area of research for researchers over decades or perhaps over centuries. In total, 15 number of factors have been identified to enhance productivity. Analytic hierarchy process approach has been appropriately chosen to rank these factors because of its simplicity and effectiveness. The tool has been used by taking perception of experts from the Indian manufacturing industry. Positive attitude and involvement of management, proactive employees, and good working conditions have been ranked as top three factors as per the experts' opinion. The ranking of factors to enhance productivity, categorization of the factors into four perspectives, and hierarchy of perspective and action plan as a final outcome of the paper may help academia and operations managers toward effective management of "operations and production activities of firms/supply chains."